PENGEMBANGAN LKS BERBASIS KOLABORATIF UNTUK MENGKATKAN KETERAMPILAN PROSES SAINS PADA SISWA DI MAN 3 JEMBER - Iinamy Nurul Fuad; Sri Astutik; Agus abdul ghani (JURNAL PEMBELAJARAN FISIKA, 2018)
Learning is a relatively permanent process of change resulting from experience. While the teaching materials can help students to be actively involved in learning activities one of them is the student worksheet (LKS). Student Worksheet (LKS) can be used as teaching materials that make students more active. Collaborative learning process can facilitate students in learning, each group member can learn from each other, even teachers can learn from their students. While the science process skill is a set of skills used in conducting investigations to find concepts, principles or theories. The purpose of his research was intended to know the validity of LKS, effectiveness of learning out came, and ability of science process skill after using LKS. Based on data analysis that LKS (Student Worksheet) was disseminated in valid category is 4.06. The effectiveness of LKS with amounting to 35 students with the average pre-test value 46.45 and posttest 75.72. Data analysis of both pre-test and post-test data in N-gain test show that significant result that is 0.5 with moderate criterion in science skill skill of XI IPA I MAN 3 Jember.Key words: Collaborative Learning, LKS, Process Science Skills.